ANALISIS LOGAM BERAT (Mn,Pb,Cu,Fe) PADA AIR DAN SEDIMEN DI PERAIRAN SUNGAI KUIN KOTA BANJARMASIN - Muhammad Asrin Wibowo; Mijani Rahman; Idiannor Mahyudin; Fatmawati Fatmawati (Universitas Lambung Mangkurat, 2022)
The Kuin River is a small river located in Banjarmasin, South Kalimantan. Various land use activities in the Kuin River area such as residential activities are thought to have affected the water quality of the Kuin River. This study aims to analyze the content of heavy metals (Pb, Cu, Fe, Mn) in water bodies and sediments in the waters of the Kuin River, Banjarmasin City. The research was conducted in River Kuin, District, Banjarmasin City, South Kalimantan Province. Determination of the research location in Table 1 uses the Purposive Sampling Method, which is a method of taking samples from a population. The location of observations was recorded using a Global Positioning System (GPS) tool. Based on the results of this study, the waters of the Kuin River Banjarmasin contained a heavy metal content of Manganese (Mn) obtained in water as much as <0.03 mg/L. The heavy metal content of Manganese (Mn) in the sediment is 5.6 - 19.8 mg/kg. Meanwhile, the heavy metal content of Lead (Pb) obtained in water was < 0.03 mg/L. The heavy metal content of Lead (Pb) in the sediment is 5.6 - 19.8 mg/kg. In addition, in the waters of the Kuin River Banjarmasin there is a heavy metal content of Copper (Cu) obtained in water as much as <0.03 mg/L. The heavy metal content of Copper (Cu) in the sediment is 5.6 - 19.8 mg/kg. Heavy metal Iron (Fe) obtained in water is < 0.03 mg/L. The heavy metal content of Iron (Fe) in the sediment is 5.6 - 19.8 mg/kg.